2020
DOI: 10.1177/1477370820980448
|View full text |Cite
|
Sign up to set email alerts
|

The financial management of cocaine trafficking in Italy

Abstract: Drawing on a set of empirical data, including in-depth interviews with law enforcers and public prosecutors, the article provides preliminary and detailed information on the structure, social organization of actors and financial management of cocaine trafficking in Italy. The article aims to increase knowledge on the financing mechanisms of organized crime activities and uses the Italian cocaine market as a case example. The findings suggest that the national market is fragmented into an interplay of actors wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Contrary to earlier findings on the cocaine trade by Krekel (2019), the financial transactions consist of more than just direct cash or underground banking transactions as it is shown that bartering and banking transfers are also used (see also Terenghi, 2020). However, information about other payment methods, that is, cryptocurrency and tradebased money laundering (TBML) are absent in the analysis.…”
Section: Toward Financial Crime Scriptingmentioning
confidence: 68%
See 1 more Smart Citation
“…Contrary to earlier findings on the cocaine trade by Krekel (2019), the financial transactions consist of more than just direct cash or underground banking transactions as it is shown that bartering and banking transfers are also used (see also Terenghi, 2020). However, information about other payment methods, that is, cryptocurrency and tradebased money laundering (TBML) are absent in the analysis.…”
Section: Toward Financial Crime Scriptingmentioning
confidence: 68%
“…Besides law enforcement agencies sometimes paying relatively little attention to the financial management of the cocaine trade, research on this topic is also scarce (Hall and Antonopoulos, 2017; Terenghi, 2020). Therefore, given the importance of enhancing a financial approach to (organized) crimes, this article builds on crime script analysis as a way to develop financial crime scripts.…”
Section: Introductionmentioning
confidence: 99%